Polyphase deformation history of the “Tibetan Sedimentary Sequence” in the Himalayan chain (South-East Tibet) - Montomoli, Chiara; Appel, Erwin; Borja, Antolin; Dunkl, István; El Bay, Rachida; Ding, Lin; Gloaguen, R (Himalayan Journal of Sciences, 2008)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!–[if gte mso 10]> <![endif]–> DOI = 10.3126/hjs.v5i7.1285 Himalayan Journal of Sciences Vol.5(7) (Special Issue) 2008 p.91